2023
DOI: 10.1002/tqem.21970
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted synthesis of Fe‐TiO2 and Ce‐TiO2 catalysts and subsequent application for photocatalytic, sonocatalytic, and sonophotocatalytic decolorization of basic Victoria blue dye

Abstract: Synthesis of Fe‐TiO2 and Ce‐TiO2 catalysts using conventional, and ultrasound assisted (US) homogeneous coprecipitation method has been investigated. Effects of ultrasonic irradiation time and ultrasonic power on catalyst synthesis were studied and it was elucidated that best conditions were 140 W and 60 min, respectively. Characterization using FE‐SEM revealed spherical particles with the size range from 36.4 to 49.4 nm whereas XRD analysis affirmed a mixture of anatase, rutile, and brookite TiO2 phase with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Dey and Gogate [68] , investigated the effect of the synthesis method of Fe-TiO 2 and Ce-TiO 2 structures. A conventional (C) and an ultrasound assisted (US) homogeneous coprecipitation method was used and it was observed that the intensification improves the crystallinity, lowers the particle size (1270 and 1170 nm for Ce-TiO 2 (C) and Fe-TiO 2 (C), and 584 and 449 nm for the Ce-TiO 2 (US) and Fe-TiO 2 (US), respectively) and increases the surface area of the catalyst in the case of Ce-TiO 2 (US) (185.65 m 2 /g).…”
Section: Sonochemical Synthesis Of Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dey and Gogate [68] , investigated the effect of the synthesis method of Fe-TiO 2 and Ce-TiO 2 structures. A conventional (C) and an ultrasound assisted (US) homogeneous coprecipitation method was used and it was observed that the intensification improves the crystallinity, lowers the particle size (1270 and 1170 nm for Ce-TiO 2 (C) and Fe-TiO 2 (C), and 584 and 449 nm for the Ce-TiO 2 (US) and Fe-TiO 2 (US), respectively) and increases the surface area of the catalyst in the case of Ce-TiO 2 (US) (185.65 m 2 /g).…”
Section: Sonochemical Synthesis Of Photocatalystsmentioning
confidence: 99%
“…
Fig. 6 FESEM images of catalysts obtained using different approaches (a) Ce-TiO 2 (C), (b) Ce-TiO 2 (US), (c) Fe-TiO 2 (C), (d) Fe-TiO 2 (US) [68] .
…”
Section: Sonochemical Synthesis Of Photocatalystsmentioning
confidence: 99%
“…2 Although there are different physical and chemical treatment methods available that have been reviewed for the treatment of wastewater, they are associated with different performance characteristics, generation of secondary wastes and high treatment costs. [3][4][5] In recent times, advanced oxidation processes (AOPs) have been extensively studied for the degradation of various pollutants as they mainly produce hydroxyl radicals ( • OH) also resulting in the formation of superoxide radicals (O 2…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many developing countries, the bulk of domestic and industrial wastewater is directly discharged into natural streams without any treatment processes or after primary treatment only as a consequence of high treatment costs, causing severe health and environmental concerns 2 . Although there are different physical and chemical treatment methods available that have been reviewed for the treatment of wastewater, they are associated with different performance characteristics, generation of secondary wastes and high treatment costs 3‐5 . In recent times, advanced oxidation processes (AOPs) have been extensively studied for the degradation of various pollutants as they mainly produce hydroxyl radicals ( • OH) also resulting in the formation of superoxide radicals (O 2 •− ) and hydroperoxyl radicals ( • OOH), driving the degradation of pollutants 6,7 .…”
Section: Introductionmentioning
confidence: 99%